Government’s Role After the 374/PDT.G/LH/2019/PN.JKT.PST Decision concerning Jakarta’s Air Pollution in the Context of Environmental Recovery - Netty Naiborhu; Josua Hari M (Universitas Muhammadiyah Surakarta, 2022)
ABSTRACT Purpose of the study: This study aims to realize state responsibility through implementing government authority to court decisions in restoring the right to a good and healthy environment. Method: This study utilized a normative juridical method with a statutory approach and decision analysis. Results: In the settlement of environmental disputes, the error-based recovery approach aims to create fair law enforcement. Applications of this study: This research serves as a reference for the government in making policies and dispute resolution. Hence, the settlement of environmental disputes is not only based on errors but also risk. Novelty/ Originality: Mechanisms for resolving environmental issues will be discovered through environmental recovery, allowing the law to work for the benefit of humankind. Thus, the law is not solely anthropocentric but also ecocentric following the environmental recovery approach. Keywords: State Responsibility, Government Authority, Environmental Recovery